Histopathological and prognostic significance of the expression of sex hormone receptors in bladder cancer: A meta-analysis of immunohistochemical studies - Ide, Hiroki; Inoue, Satoshi; Miyamoto, Hiroshi (PloS one, 2017)
Emerging preclinical evidence suggests the involvement of sex hormones and their receptor signals in the development and progression of bladder cancer. Meanwhile, previous studies have demonstrated conflicting results on the relationship between the status of sex hormone receptors in urothelial tumors and histopathological characteristics of the tumors or patient outcomes. We therefore conducted this meta-analysis to assess the clinicopathological impact of the expression of androgen receptor (AR) and estrogen receptors (ERs) in bladder cancer. A comprehensive literature search in databases (i.e. PubMed, Web of Science, Cochrane) was performed for all immunohistochemical studies stained for AR, ERα, and/or ERβ in surgically resected bladder cancer specimens and analyzed for patient outcomes. We selected eligible studies in accordance with the PRISMA guidelines and analyzed data using R software. A total of 2,049 patients from 13 retrospective studies were included in this meta-analysis. The difference in ERα expression between non-tumors and tumors was significant [odds ratio (OR) = 0.412; P<0.001], while those of AR (OR = 3.256; P = 0.336) or ERβ (OR = 0.580; P = 0.674) were not statistically significant. AR positivity in tumors was strongly correlated with gender (male vs. female: OR = 0.658; P = 0.027) or tumor grade (low-grade vs. high-grade: OR = 0.575; P<0.001). ERβ positive rates were significantly higher in high-grade (OR = 2.169; P<0.001) and muscle-invasive (OR = 3.104; P<0.001) tumors than in low-grade and non-muscle-invasive tumors, respectively. Survival analysis in patients with non-muscle-invasive bladder cancer revealed associations between AR expression and better recurrence-free survival [hazard ration (HR) = 0.593; P = 0.006) as well as between ERβ expression and worse recurrence-free (HR = 1.573; P = 0.013) or progression-free (HR = 4.148; P = 0.089) survivals. These data suggest down-regulation of ERα expression in bladder tumors, compared with non-neoplastic urothelial tissues. AR or ERβ expression was down- or up-regulated, respectively, in high-grade and/or muscle-invasive bladder cancers. Moreover, immunohistochemistry of AR/ERβ in surgical specimens may serve as prognosticators in patients with non-muscle-invasive bladder tumor.